Pendirian BPRS di Kota Banjarmasin Dalam Perspektif Yuridis dan Pengembangan Ekonomi - Muhaimin Muhaimin (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine and analyze plans for establishing a BPRS in the City of Banjarmasin in terms of juridical aspects and economic potential. The data used is primary and secondary data. Primary data is in the form of questionnaires and interviews distributed to business actors and individuals, while secondary data is data taken from the Financial Services Authority (OJK), Bank Indonesia, and the South Kalimantan Central Statistics Agency. The data analysis used is a mixed method by combining qualitative descriptive analysis and quantitative analysis. The research results show that from a juridical aspect the BPRS in Banjarmasin City is worthy of being established. The legal entity of a BPRS can legally be in the form of a BUMD or Regional Liability Company. From the aspect of economic and market potential, the Banjarmasin City BPRS has the potential to be established. This potential can be seen from the development of GRDP per capita, economic growth and distribution of GRDP percentages, as well as analysis of market competitors. Keywords: BPRS, juridical, economic potential